2020
DOI: 10.20965/jrm.2020.p0798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gait Inducing Assist for Patients with Parkinson’s Disease on Double Support Phase During Gait

Abstract: Parkinson’s disease (PD) is a common progressive neurodegenerative disease that affects a wide range of motor and non-motor symptoms. Freezing of gait (FOG) is such a motor symptom of PD that frequently results in falling, and almost half of PD patients suffer from FOG. In this study, we investigated the effectiveness of a robotic assistance system called UPS-PD, which was developed to suppress FOG. The double limb support phase (DLS) in a 10-m straight-line walking task, the gait time and step counts were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The study [11] reported that using a pedal-powered wheelchair COGY, PD patients can demonstrate regular and fast pedal movements without having FOG. Motivated by the results with COGY, Higuchi, et al previously developed a novel pneumatic walking assist device that gives self-paced and self-induced tactile and force feedback on the knee, and showed its efficacy on the double support phase during the gait of PD patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…The study [11] reported that using a pedal-powered wheelchair COGY, PD patients can demonstrate regular and fast pedal movements without having FOG. Motivated by the results with COGY, Higuchi, et al previously developed a novel pneumatic walking assist device that gives self-paced and self-induced tactile and force feedback on the knee, and showed its efficacy on the double support phase during the gait of PD patients [12].…”
Section: Introductionmentioning
confidence: 99%